Turbine Characteristics of Wave Energy Conversion Device for Extraction Power Using Breaking Waves - Paresh Halder; Hideki Takebe; Krisna Pawitan; Jun Fujita; Shuji Misumi; Tsumoru Shintake (Energies, 2020)
A new type of wave energy converter which harnesses electricity from onshore breaking waves has been studied at Okinawa Institute of Science and Technology Graduate University (OIST) since 2014. This concept has been demonstrated at a coral beach on the Maldives since 2018. Wave energy conversion is possible when waves approaching the shore steepen due to decreased water depth resulting in wave breaks near the surface. A steepened wave reaches the critical velocity of 4~6 m/sec shoreward before it breaks. A rotating blade takes advantage of this breaking phenomenon to convert the wave energy into electricity. The work presented here includes an experimental and numerical investigation of a prototype model of the wave energy converter. The turbine having five blades of variable chord lengths, twist angles, and constant thickness profile from hub to tip was simulated under similar flow as well as testing conditions, to predict the turbine performance. A commercial computational fluid dynamic tool SolidWorks Flow Simulation 2018 was used for the simulations at various rotation speeds with a uniform inlet velocity. The modified k-ε with a two-scale wall function turbulence closure model was selected. The validation performed for different test cases showed that the present computational results match in good agreement with the experimental results. Additionally, details performance of the turbine running, and generator characteristics have been reported in this paper.